Loss of PUMA (BBC3) does not prevent thrombocytopenia caused by the loss of BCL‐XL (BCL2L1). (25th May 2016) - Delbridge, Alex R. D.; Chappaz, Stephane; Ritchie, Matthew E.; Kile, Benjamin T.; Strasser, Andreas; Grabow, Stephanie
Summary: Apoptosis is required to maintain tissue homeostasis in multicellular organisms. Platelets, the anucleate cells that are essential for blood clotting, are a prime example. Their brief life span in the circulation is regulated by the intrinsic apoptosis pathway. Pro‐survival BCL‐XL (also termed BCL2L1) is essential for platelet viability. It functions to restrain the pro‐apoptotic BCL‐2 family members BAK (also termed BAK1) and BAX, the essential mediators of intrinsic apoptosis. Genetic deletion or pharmacological inhibition of BCL‐XL results in thrombocytopenia. Conversely, deletion of BAK in platelets doubles their circulating life span. However, what triggers platelet apoptosis in vivo remains unclear. The pro‐apoptotic BH3‐only proteins are essential for initiating apoptosis in nucleated cells, and there is some evidence to suggest they also play a role in platelet biology. We investigated whether PUMA (also termed BBC3), a potent BH3‐only protein that can inhibit all pro‐survival BCL‐2 family members as well as directly activate BAX, regulates the death of platelets. Surprisingly, loss of PUMA had no impact on the loss of platelets caused by loss of BCL‐XL. It therefore remains to be established whether other BH3‐only proteins play a critical role in induction of apoptosis in platelets or whether their death is controlled solely by the interactions between BCL‐XL with BAK and BAX.